EFEKTIFITAS MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP HASIL BELAJAR IPA PESERTA DIDIK KELAS V SD INPRES PARE’-PARE’ KECAMATAN BAJENG KABUPATEN GOWA - Nurul Hikmah; Irmawanty Irmawanty; Anisa Anisa (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
This type of research is quantitative with a pre-experimental research design in the form of One Group pretest-posttest. This study aims to determine the effectiveness of the guided inquiry learning model by teaching material properties of objects in class V SD Inpres Pare'-pare', in terms of the achievement of mastery of learning outcomes; student activity in participating in learning; and students' responses to the use of inquiry learning models. This study uses two observed variables, namely the independent variable (X) in this study is the learning model, namely the guided inquiry learning model and the dependent variable (Y) in this study is the result of learning science in grade V SD Inpres Pare'-Pare'. The population of this study were fifth grade students of SD Inpres Pare'-Pare'. The sampling technique used is saturated sampling technique, by making the population a sample of 20 students. The research instruments used were learning achievement tests, activity sheets, and response sheets, while the data collection techniques in this study used learning achievement tests, documentation and observation. The data analysis used was descriptive statistical data analysis, activity data analysis and student response data analysis. The results of this study indicate that the average posttest result is 94. As for the percentage of student activity after the use of the guided inquiry learning model is 82% and for the positive response of students to the use of the guided inquiry learning model is 96%. Based on the results of the research above, it can be concluded that the results of research on the use of effective guided inquiry learning models are used in learning science material on the properties of objects in class V SD Inpres Pare'-Pare', Bajeng District, Gowa Regency.